Electrode material, and method of producing electrode material
By performing alkaline treatment and surface oxidation treatment on a specific NiAl-based alloy, Raney nickel with high catalytic activity was prepared, which solved the problem of insufficient catalyst activity in existing water electrolytic devices and achieved an efficient water electrolytic process.
Patent Information
- Application Number
- JP2023175273
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
AI Technical Summary
The Raney nickel catalyst in existing water electrolysis devices has problems of insufficient activity and poor material stability during high-efficiency water electrolysis.
By alkaline treatment of a specific NiAl-based alloy, Raney nickel with excellent catalytic activity is prepared. The specific steps include using a NiAl-based alloy containing copper and iron, and reacting in a high temperature and high concentration alkaline environment, and then surface oxidation treatment of the prepared Raney nickel.
The high activity and stability of the catalyst in the water electrolytic device is achieved, the efficiency of oxygen and hydrogen is improved, and the resistance and short circuit risk during the electrolysis process is reduced.
Smart Images

Figure 2025065817000003 
Figure 2025065817000004 
Figure 2025065817000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode material used in electrodes of a water electrolysis device, and a method for producing the electrode material. [Background technology]
[0002] Water electrolysis is the electrolysis of water into hydrogen and oxygen, and is used, for example, as a technology for producing hydrogen. A water electrolysis device for generating hydrogen has, for example, an electrolytic cell containing an electrolytic solution such as alkaline water, and an anode and a cathode arranged in the electrolytic cell with a separator sandwiched therebetween. In the water electrolysis device, oxygen is generated at the anode and hydrogen is generated at the cathode by passing a current between the anode and the cathode.
[0003] Patent Document 1 discloses a technology that uses Raney nickel as a catalyst for the anode of the water electrolysis device. Raney nickel is nickel that remains after dissolving and removing only aluminum from a NiAl-based alloy containing nickel and aluminum by alkali treatment. Raney nickel is a porous body with a large specific surface area in which a large number of pores are formed by dissolving aluminum. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 01-028837 Summary of the Invention [Problem to be solved by the invention]
[0005] As a result of extensive research, the present inventors have found that Raney nickel obtained from a NiAl-based alloy of a specific composition exhibits high activity as a catalyst for use in electrodes of a water electrolysis device. [Means for solving the problem]
[0006] The manufacturing method of the electrode material for solving the above problems is a manufacturing method of an electrode material used for an electrode of a water electrolysis device, and has an alkali treatment step of obtaining Raney nickel by eluting aluminum from the NiAl-based alloy by treating the NiAl-based alloy with an alkali substance. The NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x (x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0 ≤ y ≤ 0.35.) It is an alloy represented by.
[0007] In the above manufacturing method, the NiAl-based alloy has a composition formula Al4Ni (3-x) Co x (x is a value satisfying 0.3 ≤ x ≤ 1.5.) It is preferably an alloy represented by. In the above manufacturing method, the NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x (x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0 < y ≤ 0.35.) It is preferably an alloy represented by.
[0008] In the above manufacturing method, the NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x (x and y are values satisfying 0.5 ≤ x ≤ 1.5 and 0 < y ≤ 0.2.) It is preferably an alloy represented by.
[0009] In the above manufacturing method, the NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x (x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0.05 < y ≤ 0.15.) It is preferably an alloy represented by.
[0010] In the above manufacturing method, the alkaline treatment step includes a treatment of reacting an alkaline aqueous solution, which is an aqueous solution of the alkaline substance, with the NiAl-based alloy at a temperature of 100°C or higher, the alkaline substance is an alkali metal hydroxide, and the concentration of the alkaline aqueous solution is preferably 3M or higher.
[0011] In the above manufacturing method, the alkaline treatment step includes a treatment of reacting an alkaline aqueous solution, which is an aqueous solution of the alkaline substance, with the NiAl-based alloy at a temperature of 140°C or higher, the alkaline substance is an alkali metal hydroxide, and the concentration of the alkaline aqueous solution is preferably 14M or higher.
[0012] The above-mentioned production method preferably includes an oxidation step of oxidizing the surface of the Raney nickel obtained in the alkali treatment step. The electrode material that solves the above problems is an electrode material used in electrodes of a water electrolysis device, and contains Raney nickel in which the molar ratio of nickel, iron, and cobalt (nickel:iron:cobalt) is (3-(x+y)):y:x (x and y are values that satisfy 0.3≦x≦1.5, 0≦y≦0.35). Effect of the Invention
[0013] According to the present invention, a material for a water electrolysis electrode exhibiting high activity can be obtained. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a graph showing the evaluation results of the catalytic activity in Test 1. [Diagram 2] FIG. 2 is a graph showing the evaluation results of the catalytic activity in Test 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, one embodiment of the method for producing an electrode material of the present invention will be described. In this specification, "A to B" given as a numerical range means "A or more and B or less". The electrode material produced by the production method of this embodiment is a catalyst used in the electrodes of a water electrolysis device. The electrode material can be used in either the oxygen generating electrode, which is the anode, or the hydrogen generating electrode, which is the cathode, of the water electrolysis device. It is particularly preferable to use the electrode material in the oxygen generating electrode, which is the anode.
[0016] The method for producing an electrode material of this embodiment includes an alkali treatment step for obtaining Raney nickel from a NiAl-based alloy, and an oxidation step for oxidizing the surface of the Raney nickel obtained in the alkali treatment step. The oxidation step can be omitted as necessary. In the following, the Raney nickel obtained in the alkali treatment step before the oxidation step may be referred to as the first Raney nickel. And the Raney nickel after the oxidation step may be referred to as the second Raney nickel. In this specification, the NiAl-based alloy means a group of alloys containing Ni and Al as constituent metals. The NiAl-based alloy may contain constituent metals other than Ni and Al. Unless there is a description specifying the ratio of the constituent metals, the NiAl-based alloy includes various alloys having different ratios of the constituent metals.
[0017] <Alkaline treatment process> The alkali treatment step is a step of treating a NiAl-based alloy of a specific composition (hereinafter, referred to as specific NiAl-based alloy) with an alkaline substance to dissolve aluminum from the NiAl-based alloy, thereby obtaining the first Raney nickel.
[0018] (Specific NiAl-based alloy) The specific NiAl-based alloy subjected to the alkaline treatment process has the composition formula Al4Ni (3-(x+y)) Fe y Co x In the above formula, x and y are values that satisfy 0.3≦x≦1.5 and 0≦y≦0.35. Hereinafter, x in the above formula may be referred to as Co ratio or Co ratio x. Similarly, y in the above formula may be referred to as Fe ratio or Fe ratio y.
[0019] Raney nickel used as an electrode material for water electrolysis equipment exerts catalytic activity by generating complex (acid) hydroxides during operation. The complex (acid) hydroxides are, for example, a complex of at least two of Ni(O)OH, Fe(O)OH, Al(O)OH, and Co(O)OH.
[0020] The Raney nickel obtained from the specific NiAl-based alloy with a Co ratio x of 0.3 or more can generate a more active complex (acid) hydroxide during the operation of the water electrolysis device, and is also likely to form a structure with many interfaces between NiOOH and CoOOH. Therefore, by making the Co ratio x 0.3 or more, a Raney nickel exhibiting high activity can be obtained. In addition, the Co ratio x is preferably 0.5 or more.
[0021] Raney nickel obtained from a specific NiAl-based alloy with a Co ratio x of 1.5 or less can suppress the dissolution of cobalt ions into the electrolyte during operation of the water electrolysis device. Therefore, it is possible to suppress the increase in resistance caused by clogging of the separator by the dissolved cobalt ions. In addition, the dissolved cobalt ions may cause an internal short circuit by depositing as metallic cobalt on the cathode surface in the form of dendrites on the cathode side. Therefore, by suppressing the dissolution of cobalt ions, it is possible to suppress a short circuit within the cell.
[0022] The Raney nickel obtained from the specific NiAl-based alloy with the Fe ratio y set to 0.35 or less can suppress the dissolution of iron ions into the electrolyte during the operation of the water electrolysis device. Therefore, the increase in resistance caused by the clogging of the separator by the dissolved iron ions can be suppressed. In addition, the dissolved iron ions may react with the oxygen gas generated on the anode side and precipitate as iron oxide (e.g., Fe2O3) on the anode surface. Since this iron oxide has a lower oxygen generation activity than the anode, the precipitation of iron oxide on the anode surface causes a decrease in the activity of the anode. In addition, the dissolved iron ions may cause an internal short circuit by precipitating in the form of dendrites on the cathode surface as iron oxide (e.g., Fe3O4) having electronic conductivity on the cathode side. Therefore, by suppressing the dissolution of iron ions, the decrease in activity on the anode side and the internal short circuit can be suppressed. In addition, the Fe ratio y is preferably 0.2 or less.
[0023] Next, the phases constituting the specific NiAl-based alloy will be described. (3-(x+y)) Fe y Co x The specific NiAl-based alloy represented by means of Al4Ni is an alloy of aluminum, nickel, and cobalt, or an alloy of aluminum, nickel, iron, and cobalt, in which the molar ratio of aluminum, nickel, iron, and cobalt in the entire alloy (aluminum:nickel:iron:cobalt) is 4:(3-(x+y)):y:x. Therefore, the specific NiAl-based alloy is represented by Al4Ni (3-(x+y)) Fe y Co x The alloy may be an alloy composed of a single phase, or an alloy composed of multiple phases, for example, an alloy including a main phase and a subphase.
[0024] In this specification, the main phase of the specific NiAl-based alloy means one or two specific phases that occupy most of the specific NiAl-based alloy. The main phase of the specific NiAl-based alloy can be defined as a phase that satisfies at least one of the volume condition and area condition described below.
[0025] Volume condition: The volume ratio of one specific phase in the entire alloy, or the sum of the volume ratios of two phases with the largest volume ratios in the entire alloy, exceeds 50%. The above value regarding the volume condition may be 60% or more, 70% or more, 80% or more, or 90% or more. The volume of each phase constituting the alloy can be calculated, for example, by Rietveld analysis of the X-ray diffraction (XRD) measurement data of the alloy.
[0026] Area condition: the area ratio of a specific phase in any cross section formed by splitting the alloy, or the sum of the area ratios of two phases with the largest area ratios in the cross section, exceeds 50%. The above numerical value regarding the area condition may be 60% or more, 70% or more, 80% or more, or 90% or more. The area of each phase in the above cross section of the alloy can be calculated by image analysis of elemental mapping data of the alloy cross section obtained by, for example, scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX).
[0027] [1st NiAl-based alloy] An example of a specific NiAl-based alloy is the alloy of formula Al4Ni (3-x) Co x The alloy is represented by the formula (hereinafter, referred to as the first NiAl-based alloy).
[0028] The Co ratio x of the first NiAl-based alloy is, for example, 0.3 or more, preferably 0.5 or more, and more preferably 1.0 or more. The Co ratio x of the first NiAl-based alloy is, for example, 1.5 or less, and preferably 1.2 or less. By setting the Co ratio x of the first NiAl-based alloy to 0.3 or more, a Raney nickel exhibiting high activity can be obtained. By setting the Co ratio x of the first NiAl-based alloy to 1.5 or less, a decrease in the strength of the Raney nickel resulting from a decrease in the proportion of nickel in the Raney nickel obtained from the first NiAl-based alloy can be suppressed.
[0029] Examples of the single phase, the main phase, and the subphase constituting the first NiAl-based alloy include an Al4Ni3 phase, an AlNi phase, and an Al3Ni2 phase. The first NiAl-based alloy may also include a subphase that is inevitably formed during manufacturing. The single phase, the main phase, and the subphase may include a metal other than Ni and Al. For example, the Al4Ni3 phase may be a phase in which a part of the Ni site is replaced by Co. Examples of the first NiAl-based alloy include an alloy in which the main phase is an Al4Ni3 phase and the molar ratio (aluminum:nickel:cobalt) is 4:(3-x):x.
[0030] Among the phases that the first NiAl-based alloy may contain, the Al4Ni3 phase and the AlNi phase are the first specific phases. The total ratio of the first specific phase in the first NiAl-based alloy under the above volumetric or area conditions is preferably 80% or more, 85% or more, 90% or more, 95% or more, or 100%. The Al4Ni3 phase and the AlNi phase, which are the first specific phases, have a lower Al ratio than other phases such as the Al3Ni2 phase. Therefore, the first NiAl-based alloy with a high ratio of the first specific phase has a low Al ratio. When the first NiAl-based alloy with a high ratio of the first specific phase is used, a Raney nickel with high strength is obtained due to the low Al ratio.
[0031] The first NiAl-based alloy in which the total proportion of the first specific phase falls within the above range is easily obtained by lowering the Co ratio x. When the total proportion of the first specific phase is increased, the Co ratio x is, for example, 1.2 or less, and preferably 1.0 or less. In particular, when the Co ratio x is 0.8 to 1.2, the total proportion of the above-mentioned first specific phase is 90% or more. Furthermore, when the Co ratio x is 1, almost 100% of the phases contained in the first NiAl-based alloy are Al4Ni3 phases.
[0032] [Second NiAl-based alloy] An example of a specific NiAl-based alloy is the alloy of formula Al4Ni (3-(x+y)) Fe y Co x The alloy is represented by the formula (hereinafter, referred to as the second NiAl-based alloy).
[0033] The Co ratio x and the Fe ratio y of the second NiAl-based alloy are values that satisfy, for example, 0.3 ≤ x ≤ 1.5 and 0 < y ≤ 0.35. The Co ratio x of the second NiAl-based alloy is, for example, 0.3 or more, preferably 0.5 or more, and more preferably 1.0 or more. The Co ratio x of the second NiAl-based alloy is, for example, 1.5 or less, preferably 1.2 or less. By setting the Co ratio x of the second NiAl-based alloy to 0.3 or more, Raney nickel showing high activity can be obtained. By setting the Co ratio x of the second NiAl-based alloy to 1.5 or less, a decrease in the strength of Raney nickel caused by a decrease in the proportion of nickel in the Raney nickel obtained from the first NiAl-based alloy can be suppressed. By setting the Co ratio x of the second NiAl-based alloy to 1 to 1.5, with respect to the Raney nickel obtained from the second NiAl-based alloy, the effect of improving the activity by containing cobalt and the effect of suppressing the decrease in strength caused by containing cobalt can be made compatible at a high level.
[0034] The Fe ratio y of the second NiAl-based alloy is, for example, more than 0, preferably 0.05 or more, and more preferably 0.08 or more. The Fe ratio y of the second NiAl-based alloy is, for example, 0.35 or less, preferably 0.2 or less, more preferably 0.15 or less, and even more preferably 0.12 or less. The Fe ratio y of the second NiAl-based alloy is preferably more than 0 and 0.2 or less, more preferably 0.05 to 0.15, and even more preferably 0.08 to 0.12.
[0035] By setting the Fe ratio y of the second NiAl-based alloy to 0.35 or less, a Raney nickel exhibiting high activity can be obtained. By setting the Fe ratio y of the second NiAl-based alloy to 0.2 or less, even when both cobalt and iron are contained in the Raney nickel obtained from the second NiAl-based alloy, the effect of improving activity due to the inclusion of cobalt can be obtained. Furthermore, when the Fe ratio y of the second NiAl-based alloy is set to more than 0 and 0.2 or less, particularly when it is set to 0.05 to 0.15, and further when it is set to 0.08 to 0.12, a Raney nickel exhibiting even higher activity can be obtained.
[0036] In particular, Raney nickel obtained from a specific NiAl-based alloy with an Fe ratio y of 0.05 or more can generate a large amount of highly active Fe(O)OH during operation of a water electrolysis device, and is likely to form a core-shell structure containing a relatively large amount of Fe(O)OH on the surface side. Therefore, by setting the Fe ratio y to 0.05 or more, Raney nickel showing high activity can be obtained.
[0037] The ratio of nickel in the second NiAl-based alloy, i.e., "3-(x+y)", is, for example, 1.3 or more, preferably 1.65 or more, and more preferably 1.68 or more. "3-(x+y)" is, for example, 2.45 or less. In other words, x+y is, for example, 1.7 or less, preferably 1.35 or less, and more preferably 1.32 or less. x+y is, for example, 0.55 or more.
[0038] In the second NiAl-based alloy, the ratio of cobalt to nickel (x / (3-(x+y))) is, for example, 0.11 to 1.3, preferably 0.2 to 1.15, and more preferably 0.8 to 1.2. The ratio of iron to nickel (y / (3-(x+y))) is, for example, more than 0 and 0.3 or less, preferably more than 0 and 0.2 or less, and more preferably 0.05 to 0.15. The ratio of iron to cobalt (y / x) is, for example, more than 0 and 1.17 or less, preferably more than 0 and 0.4 or less, more preferably 0.04 to 0.19, and even more preferably 0.05 to 0.15.
[0039] Examples of the single phase, the main phase, and the subphase constituting the second NiAl-based alloy include an Al4Ni3 phase, an AlNi phase, and an Al3Ni2 phase. The second NiAl-based alloy may also include a subphase that is inevitably formed during manufacturing. The single phase, the main phase, and the subphase may include a metal other than Ni and Al. For example, the Al4Ni3 phase may be a phase in which a part of the Ni site is replaced by Co. Examples of the second NiAl-based alloy include an alloy in which the main phase is an Al4Ni3 phase and the molar ratio (aluminum:nickel:iron:cobalt) is 4:(3-(x+y)):y:x.
[0040] Among the phases that the second NiAl-based alloy may contain, the Al4Ni3 phase and the AlNi phase are the second specific phases. The total proportion of the second specific phase in the second NiAl-based alloy under the above volumetric or area conditions is preferably 80% or more, 85% or more, 90% or more, 95% or more, or 100%. The Al4Ni3 phase and the AlNi phase, which are the second specific phases, have a lower Al ratio than other phases such as the Al3Ni2 phase. Therefore, the second NiAl-based alloy with a higher proportion of the second specific phase has a lower Al ratio. When the second NiAl-based alloy with a higher proportion of the second specific phase is used, a Raney nickel with high strength is obtained due to the lower Al ratio.
[0041] The second NiAl-based alloy in which the total proportion of the second specific phase falls within the above range is easily obtained by lowering the Co ratio x. When the total proportion of the second specific phase is increased, the Co ratio x is, for example, 1.2 or less, and preferably 1.0 or less. In particular, when the Co ratio x is 0.8 to 1.2, the total proportion of the second specific phase is 90% or more. When the Co ratio x is 1, almost 100% of the phases contained in the second NiAl-based alloy are Al4Ni3 phases.
[0042] Furthermore, the second NiAl-based alloy in which the total proportion of the second specific phase falls within the above range is easily obtained by lowering the Fe ratio y. When the total proportion of the second specific phase is increased, the Fe ratio y is, for example, 0.1 or less, and preferably 0.05 or less. By lowering the Fe ratio y, it is possible to suppress the generation of a different phase other than the second specific phase. When the Fe ratio y is lowered, the generation of the different phase is suppressed, and as a result, the proportion of the second specific phase becomes relatively high.
[0043] The method for producing the specific NiAl-based alloy is not particularly limited, and any known alloy production method can be used. Examples of the method for producing the specific NiAl-based alloy include a casting method, a quenching method, a mechanical alloying method, and a sputtering method.
[0044] The specific NiAl-based alloy subjected to the alkali treatment step is, for example, in the form of a powder. The average particle size of the specific NiAl-based alloy is, for example, 1 to 150 μm. The average particle size described in this specification means the particle size at an integrated value of 50% in a particle size distribution determined by a laser diffraction / scattering method.
[0045] (Processing conditions) The alkali treatment step is carried out by reacting the specific NiAl-based alloy with an alkaline aqueous solution containing an alkaline substance. The aluminum in the specific NiAl-based alloy is dissolved by the reaction with the alkaline aqueous solution, and the first Raney nickel, which is a porous body with a large specific surface area, is obtained. A specific treatment method includes, for example, adding the powdered specific NiAl-based alloy little by little into the alkaline aqueous solution, and then stirring the alkaline aqueous solution at a predetermined temperature for a predetermined time. In addition, a treatment method may be adopted in which the specific NiAl-based alloy supported on a predetermined substrate by thermal spraying or the like is reacted with the alkaline aqueous solution.
[0046] The alkaline substance is, for example, an alkali metal hydroxide or an alkali metal salt. Examples of the alkali metal hydroxide include sodium hydroxide, potassium hydroxide, and lithium hydroxide. Examples of the alkali metal salt include sodium carbonate, potassium carbonate, and lithium carbonate. The alkaline substance is preferably an alkali metal hydroxide.
[0047] The treatment temperature in the alkali treatment step is, for example, 100 to 140°C. The treatment time in the alkali treatment step is, for example, 60 to 360 minutes. The amount of the alkaline substance used in the alkali treatment step can be appropriately set depending on the amount of aluminum contained in the specific NiAl-based alloy. The amount of the alkaline substance may be any amount that is less than, equal to, or excessive to the amount of aluminum contained in the specific NiAl-based alloy in stoichiometric terms. In addition, the solid-liquid ratio of the specific NiAl-based alloy to the alkaline aqueous solution in the alkali treatment step (specific NiAl-based alloy: alkaline aqueous solution) is, for example, 1:10 to 1:500 in mass ratio.
[0048] A preferred example of the treatment conditions for the alkali treatment step is to treat at high temperature using an alkaline aqueous solution of a high concentration of an alkali metal hydroxide. The concentration of the alkaline aqueous solution under these treatment conditions is, for example, 3M or more, preferably 7M or more, and more preferably 14M or more. The concentration of the alkaline aqueous solution under these treatment conditions is 20M or less. The treatment temperature under these treatment conditions is, for example, 100°C or more, preferably 110°C or more, and more preferably 140°C or more. The treatment temperature under these treatment conditions is, for example, 148°C or less.
[0049] In order to increase the treatment temperature, it is necessary to increase the concentration of the alkaline aqueous solution so that the boiling point of the alkaline aqueous solution is equal to or higher than the treatment temperature. For example, when the treatment temperature is 100°C or higher, the concentration of the alkaline aqueous solution is preferably 3M or higher, and when the treatment temperature is 140°C or higher, the concentration of the alkaline aqueous solution is preferably 14M or higher. In addition, it is preferable to carry out the alkaline treatment step at normal pressure. In this case, hydrogen generated during the treatment can be easily removed compared to when pressurized. In particular, it is possible to suppress the complexity of the device for removing hydrogen generated during the treatment.
[0050] The above treatment conditions make it possible to obtain a first Raney nickel exhibiting high activity. In particular, the high treatment temperature can shorten the reaction time between the alkaline aqueous solution and the specific NiAl-based alloy. The reaction time between the alkaline aqueous solution and the specific NiAl-based alloy under the above treatment conditions is, for example, 3 hours or more and 6 hours or less when the concentration of the alkaline aqueous solution is 3M or more and the treatment temperature is 100°C or more, and is, for example, 1 hour or more and 6 hours or less when the concentration of the alkaline aqueous solution is 14M or more and the treatment temperature is 140°C or more. In addition, when the specific NiAl-based alloy contains iron, the high treatment temperature makes it easier to obtain a first Raney nickel having a core-shell structure in which iron atoms are transferred to the surface of the particles in the alkali treatment step, and the surface side contains a relatively large amount of iron.
[0051] The treatment conditions in the alkali treatment step may be treatment conditions that dissolve all of the aluminum contained in the specific NiAl-based alloy, or treatment conditions that leave a portion of the aluminum undissolved.
[0052] The number of times of alkali treatment in the alkali treatment step may be one or more. When the alkali treatment is performed multiple times, the treatment conditions may be the same or may be different for each alkali treatment.
[0053] The first Raney nickel obtained by the above treatment can be recovered by performing a filtration treatment. At that time, a washing treatment may be performed as necessary. As the filtration treatment, a known solid-liquid separation treatment used in the production of Raney nickel can be applied. As the washing treatment, a known washing treatment used in the production of Raney nickel, for example, a water washing treatment, can be applied.
[0054] <Oxidation process> The surface activity of the Raney nickel obtained by the alkali treatment process is high, so it may spontaneously combust in air. Therefore, it is difficult to handle during storage, and it is necessary to store it in a solvent to avoid contact with air.
[0055] The oxidation step is a step of oxidizing the surface of the first Raney nickel obtained by the alkali treatment step. The second Raney nickel, which is the first Raney nickel with an oxidized surface, is suppressed from spontaneously combusting in air. Therefore, the second Raney nickel is easier to handle during storage, etc., than the first Raney nickel.
[0056] An example of the oxidation step is carried out by reacting the first Raney nickel with an acidic aqueous solution containing an acidic substance. A specific treatment method includes, for example, adding powdered first Raney nickel little by little to the acidic aqueous solution, and then stirring the mixture at a predetermined temperature for a predetermined time.
[0057] Examples of the acidic substance include hydrogen peroxide, sodium peroxide, sodium percarbonate, and sodium perborate. Among these, the acidic substance is preferably hydrogen peroxide.
[0058] The concentration of the acidic aqueous solution, and the treatment temperature and treatment time in the oxidation step can be appropriately set. The concentration of the acidic aqueous solution is, for example, 0.7 to 10 M. The treatment temperature in the oxidation step is, for example, 15 to 80° C. The treatment time in the oxidation step is, for example, 5 to 720 minutes. The solid-liquid ratio of the first Raney nickel to the acidic aqueous solution in the oxidation step (first Raney nickel:acidic aqueous solution) is, for example, 1:9 to 1:100 in mass ratio.
[0059] The second Raney nickel obtained by the above treatment can be recovered by performing a filtration treatment. At that time, a washing treatment may be performed as necessary. As the filtration treatment, a known solid-liquid separation treatment used in the production of Raney nickel can be applied. As the washing treatment, a known washing treatment used in the production of Raney nickel, for example, a water washing treatment, can be applied.
[0060] <Raney Nickel> The first Raney nickel and the second Raney nickel (hereinafter, sometimes referred to as the Raney nickel of this embodiment) produced by the above-mentioned production method contain nickel and cobalt in a specific ratio, or contain nickel, iron, and cobalt in a specific ratio. The ratio of nickel, iron, and cobalt in the Raney nickel of this embodiment is equal to the ratio of nickel, iron, and cobalt in the specific NiAl-based alloy used in the production. Therefore, the molar ratio of nickel, iron, and cobalt in the Raney nickel of this embodiment is (3-(x+y)):y:x. In the above molar ratio, x and y are values that satisfy 0.3≦x≦1.5 and 0≦y≦0.35.
[0061] The Raney nickel of this embodiment may contain aluminum. Here, with regard to the nickel, cobalt, iron, and aluminum contained in the Raney nickel of this embodiment, the ratio of the mass of aluminum to the total mass of nickel, cobalt, and iron (mass of aluminum / (mass of nickel+mass of cobalt+mass of iron)) is defined as the aluminum ratio. In this case, the aluminum ratio in the Raney nickel of this embodiment is, for example, 0.45 or less, preferably 0.25 or less. Moreover, the aluminum ratio is, for example, 0.03 or more, preferably 0.05 or more.
[0062] The Raney nickel in this embodiment is Al4Ni (3-(x+y)) Fe y Co x The alloy may be an alloy composed of a single phase consisting of Ni phase derived from the Ni phase, or may be an alloy composed of multiple phases, for example, an alloy containing a main phase and a subphase. For example, the Raney nickel of this embodiment obtained from a specific NiAl-based alloy containing a main phase and a subphase may have a phase derived from the main phase of the specific NiAl-based alloy and a phase derived from the subphase of the specific NiAl-based alloy. The phase derived from the main phase of the specific NiAl-based alloy is, for example, a phase in which part or all of aluminum is removed from the main phase of the specific NiAl-based alloy. The phase derived from the subphase of the specific NiAl-based alloy is, for example, a phase in which part or all of aluminum is removed from the subphase of the specific NiAl-based alloy.
[0063] Examples of the Raney nickel of this embodiment obtained from the first NiAl-based alloy include an alloy having a single phase consisting of the Al4Ni3 phase, and an alloy whose main phase is a Ni phase derived from the Al4Ni3 phase or a Ni phase derived from the AlNi phase and whose molar ratio (nickel:cobalt) is (3-x):x.
[0064] Examples of the Raney nickel of this embodiment obtained from the second NiAl-based alloy include an alloy having a single phase consisting of an Al4Ni3 phase, and an alloy whose main phase is a Ni phase derived from the Al4Ni3 phase or a Ni phase derived from the AlNi phase and whose molar ratio (nickel:iron:cobalt) is (3-(x+y)):y:x.
[0065] The BET specific surface area of the Raney nickel of this embodiment is, for example, 5 to 100 m 2 The BET specific surface area means the surface area per unit mass of Raney nickel measured by N2 adsorption using the BET method.
[0066] The average particle size of the Raney nickel in this embodiment is, for example, 0.1 to 100 μm. <effect> Next, the operation of this embodiment will be described.
[0067] According to the production method of this embodiment, Raney nickel containing cobalt in a specific ratio, or Raney nickel containing iron and cobalt in specific ratios can be obtained. When the Raney nickel of this embodiment is used as an electrode material for a water electrolysis device, i.e., as an electrode catalyst, it exhibits high catalytic activity based on the generation of a highly active complex (acid) hydroxide during operation.
[0068] In particular, the Raney nickel of this embodiment shows high activity when applied as a material for the anode of a water electrolysis device, that is, as a catalyst for oxygen generation reaction. Specifically, the Raney nickel of this embodiment has a Tafel gradient of, for example, 70 to 150 mV / dec. when applied as a catalyst for oxygen generation reaction. The Tafel gradient is obtained from a Tafel plot in which the horizontal axis is the logarithm of the oxygen generation current and the vertical axis is the overvoltage, which is the value obtained by subtracting the theoretical decomposition potential of the oxygen generation reaction from the working electrode potential. The Tafel gradient obtained from the Tafel plot in which the horizontal axis is the logarithm of the oxygen generation current, is the voltage required to increase the oxygen generation current by 10 times, and the smaller the absolute value, the higher the catalytic activity for oxygen generation.
[0069] In detail, the composition formula is Al4Ni (3-x) Co x The Raney nickel of this embodiment obtained from the first specific NiAl-based alloy represented by the formula Al4Ni has a Tafel gradient of, for example, 100 to 150 mV / dec. (3-(x+y)) Fe y Co xThe Raney nickel of the present embodiment obtained from the second specific NiAl-based alloy shown by has, for example, a Tafel slope of 70 to 150 mV / dec. The measurement of the Tafel slope can be performed by the measurement method described in the examples below.
[0070] <Effect> Next, the effects of the present embodiment will be described. (1) The manufacturing method of the electrode material used for the electrode of the water electrolysis device has an alkali treatment step of obtaining Raney nickel by eluting aluminum from a specific NiAl-based alloy by treating the specific NiAl-based alloy with an alkali substance. The specific NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x (x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0 ≤ y ≤ 0.35.) It is an alloy represented by
[0071] According to the above configuration, Raney nickel showing high catalytic activity can be manufactured when used as the electrode material of the water electrolysis device. The manufactured Raney nickel shows high oxygen evolution activity when used as the anode material of the water electrolysis device, and shows high hydrogen evolution activity when used as the cathode material.
[0072] (2) The specific NiAl-based alloy is an alloy represented by the composition formula Al4Ni (3-x) Co x In the above formula, x is a value satisfying 1.0 ≤ x ≤ 1.5. According to the above configuration, the effect of (1) above is further improved.
[0073] (3) The specific NiAl-based alloy is an alloy represented by the composition formula Al4Ni (3-(x+y)) Fe y Co x In the above formula, y is a value satisfying 0 < y ≤ 0.35, and x in the above formula is a value satisfying 1.0 ≤ x ≤ 1.5. According to the above configuration, the effect of (1) above is further improved.
[0074] (4) The specific NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fey Co x An alloy represented by x (where x is a value satisfying 0.3 ≦ x ≦ 1.5), and y in the above formula is a value satisfying 0 < y ≦ 0.2. According to the above configuration, the effect of (1) above is further improved.
[0075] (5) The specific NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x An alloy represented by x (where x is a value satisfying 0.3 ≦ x ≦ 1.5), and y in the above formula is a value satisfying 0.05 < y ≦ 0.15. According to the above configuration, the effect of (1) above is further improved.
[0076] (6) The alkali treatment step includes a treatment of reacting an alkaline aqueous solution, which is an aqueous solution of an alkali substance, with a specific NiAl-based alloy at a temperature of 100 °C or higher. The alkali substance is an alkali metal hydroxide. The concentration of the alkaline aqueous solution is 3 M or higher. According to the above configuration, in the alkali treatment step, iron atoms migrate to the surface of the particles, and it becomes easier to obtain Raney nickel having a core-shell structure containing relatively more iron on the surface side. Also, the reaction time between the alkaline aqueous solution and the specific NiAl-based alloy can be shortened.
[0077] (7) The alkali treatment step includes a treatment of reacting an alkaline aqueous solution, which is an aqueous solution of an alkali substance, with a specific NiAl-based alloy at a temperature of 140 °C or higher. The alkali substance is an alkali metal hydroxide. The concentration of the alkaline aqueous solution is 14 M or higher. According to the above configuration, the effect of (6) above is further improved.
[0078] (8) The manufacturing method of the electrode material used for the electrode of the water electrolysis device has an oxidation step of oxidizing the surface of the Raney nickel obtained by the alkali treatment step. According to the above configuration, spontaneous ignition of the obtained Raney nickel in the air can be suppressed. Thereby, Raney nickel that is easy to handle during storage etc. is obtained.
Examples
[0079] Hereinafter, a more specific embodiment of the above embodiment will be described. <Test 1> In test 1, the composition formula was Al4Ni (3-x) Co x The catalytic activity of Raney nickel obtained from a NiAl-based alloy represented by
[0080] (Preparation of Raney Nickel) A mixture of predetermined amounts of aluminum, nickel, and cobalt is heated and melted at 1600℃ in a high-frequency melting furnace, and then cooled to produce a material with a main phase of Al4Ni3 and a composition formula of Al4Ni (3-x) Co x The alloy ingots were produced with Co ratios x of 0, 0.1, 0.5, 1.0, and 1.5. The NiAl-based alloy with a Co ratio x of 0 is a NiAl-based alloy with a composition formula of Al4Ni3. The alloy ingots obtained were pulverized to obtain NiAl-based alloy powder with the above composition. The average particle size of the obtained powder was measured by a laser diffraction / scattering method and was in the range of 40 to 60 μm.
[0081] Next, the obtained NiAl-based alloy powder (2 g) was immersed in a 14 M sodium hydroxide aqueous solution (30 g) and subjected to an alkali treatment for 3 hours at 140° C. After that, a filtration treatment and a cleaning treatment with water were performed, thereby obtaining a first Raney nickel in which aluminum was dissolved from the NiAl-based alloy.
[0082] The obtained first Raney nickel powder (1.5 g) was immersed in a 5 mass% hydrogen peroxide aqueous solution (14 g) and subjected to an oxidation treatment for 10 hours at 20° C. Then, a filtration treatment and a washing treatment with water were performed to obtain a second Raney nickel powder with an oxidized surface.
[0083] (Evaluation of catalytic activity) The oxygen evolution activity of the obtained second Raney nickel was evaluated using a three-electrode electrochemical measurement device.
[0084] A slurry was prepared by dispersing powder of 2-Raney nickel, Ketjen black, and 20% Nafion (registered trademark) dispersion (DE2020CS type: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in a mixed solvent of water and ethanol. The prepared slurry was applied to a glassy carbon substrate to obtain an electrode body. The amount of 2-Raney nickel supported in the electrode body was 0.05 mg / cm. 2 It was decided.
[0085] A 7 mol / L aqueous potassium hydroxide solution was used as the electrolyte, and the platinum coil (counter electrode) and the working electrode were immersed in the electrolyte. A mercury-mercury oxide electrode was used as the reference electrode, and it was connected to the electrolyte via a liquid junction. The potential of the working electrode relative to the reference electrode was swept at 10 mV / s, and the oxygen evolution current versus the electrode potential was measured at room temperature.
[0086] Next, a Tafel plot was created with the logarithm of the measured oxygen generating current (A) on the horizontal axis and the overvoltage (V), which is the value obtained by subtracting the theoretical decomposition potential of the oxygen generating reaction from the working electrode potential, on the vertical axis, and the Tafel gradient (mV / dec.) was obtained from the created Tafel plot. The overvoltage was calculated assuming that the theoretical decomposition voltage of the oxygen generating reaction is 1.23 V. The results are shown in the graph in Figure 1. As described above, the Tafel gradient obtained by plotting the logarithm of the oxygen generating current on the horizontal axis is the amount of change in potential required to increase the oxygen generating current by 10 times. The smaller the absolute value of the Tafel gradient, the higher the catalytic activity for oxygen generation.
[0087] Table 1 below is a table summarizing the values of the Co ratio x and the Tafel slope at each point in the graph shown in FIG. 1. The relative evaluation column of oxygen generating activity in Table 1 also shows the evaluation of the oxygen generating activity for each example with different Co ratios x. This evaluation is a relative evaluation in which the value of the Tafel slope when the Co ratio x is "0" is taken as a reference value (hereinafter referred to as the first reference value). The evaluation criteria are as follows:
[0088] "X": The Tafel slope value is 105% or more relative to the first reference value. "=": the value of the Tafel slope is equal to or greater than 95% and less than 105% of the first reference value. "◯": The Tafel slope value is 80% or more and less than 95% of the first reference value.
[0089] "Excellent": The Tafel gradient value is less than 80% of the first reference value.
[0090] [Table 1] As shown in Figure 1 and Table 1, the Tafel slope is (3-x) Co x The Tafel gradient changes according to the Co ratio of the NiAl-based alloy represented by Al4Ni3. More specifically, the Tafel gradient is significantly lower in the Co ratio range of 0.5 to 1.5 compared to when the Co ratio is 0 (when a NiAl-based alloy represented by Al4Ni3 is used). The downward trend of the Tafel gradient in this range gradually decreases as the Co ratio increases, and the rate of change with increasing Co ratio becomes smaller in the Co ratio range of 1.0 to 1.5. In Test 1, the NiAl-based alloy with a Co ratio of 0.5 to 1.5 corresponds to the first NiAl-based alloy.
[0091] 1, from the downward trend of the Tafel slope relative to the increase in the Co ratio in the range of 0 to 0.5, it is considered that in the range of 0.35 or more of the Co ratio, the Tafel slope falls to 90% or less compared to when the Co ratio is 0. Therefore, it can be inferred that if the Co ratio is 0.35 or more, the Tafel slope falls significantly.
[0092] From the above results, it is found that the Raney nickel obtained from the first NiAl-based alloy containing cobalt in the Co ratio range of 0.35 to 0.15 has higher oxygen generation activity than the Raney nickel obtained from the NiAl-based alloy not containing cobalt. And, among the first NiAl-based alloys, it is found that the Raney nickel obtained from the first NiAl-based alloy containing cobalt in the Co ratio range of 0.5 to 1.5, particularly 1.0 to 1.5, exhibits particularly high oxygen generation activity.
[0093] <Test 2> In test 2, the composition formula was Al4Ni (3-(x+y)) Fe y Co x The catalytic activity of Raney nickel obtained from a NiAl-based alloy represented by
[0094] (Preparation of Raney Nickel) A mixture of predetermined amounts of aluminum, nickel, iron, and cobalt is heated and melted at 1600℃ in a high-frequency melting furnace, and then cooled to produce a material with a main phase of Al4Ni3 and a composition formula of Al4Ni (3-(x+y)) Fe y Co x The alloy ingots were prepared with a Co ratio x of 1 and Fe ratios y of 0, 0.05, 0.1, and 0.2. The NiAl-based alloy with an Fe ratio y of 0 is an NiAl-based alloy represented by the composition formula Al4Ni3Co. The alloy ingots obtained were pulverized to obtain powder of the NiAl-based alloy with the above composition. The average particle size of the obtained powder was measured by a laser diffraction / scattering method and was in the range of 40 to 60 μm.
[0095] Next, the obtained NiAl-based alloy powder (2 g) was immersed in a 14 M sodium hydroxide aqueous solution (30 g) and subjected to an alkali treatment for 3 hours at 140° C. After that, a filtration treatment and a cleaning treatment with water were performed, thereby obtaining a first Raney nickel in which aluminum was dissolved from the NiAl-based alloy.
[0096] The obtained first Raney nickel powder (1.5 g) was immersed in a 5 mass% hydrogen peroxide aqueous solution (14 g) and subjected to an oxidation treatment for 10 hours at 20° C. Thereafter, a filtration treatment and a washing treatment with water were performed to obtain a second Raney nickel powder with an oxidized surface.
[0097] (Evaluation of catalytic activity) The oxygen generating activity of the obtained second Raney nickel was evaluated in the same manner as in Test 1. The results are shown in the graph of FIG. 2. In FIG. 2, a line indicating the first reference value in Test 1 is superimposed for reference. Table 2 below is a table summarizing the values of the Fe ratio y and the Co ratio x and the Tafel gradient at each point in the graph shown in FIG. 2. The relative evaluation column of the oxygen generating activity in Table 2 also shows the evaluation of the oxygen generating activity of each example in which the Fe ratio y is different. This evaluation is a relative evaluation in which the value of the Tafel gradient when the Co ratio x is "1" and the Fe ratio y is "0" is taken as the reference value (hereinafter referred to as the second reference value). The evaluation criteria for this evaluation are as follows:
[0098] "X": The Tafel slope value is 105% or more relative to the second reference value. "=": the value of the Tafel slope is 95% or more and less than 105% of the second reference value. "◯": The value of the Tafel slope is 80% or more and less than 95% of the second reference value.
[0099] "Excellent": The Tafel gradient value is less than 80% of the second reference value.
[0100] [Table 2] As shown in Figure 2 and Table 2, the Tafel slope is (3-(x+y)) Fe y Co xThe Tafel gradient changes according to the Fe ratio of the NiAl-based alloy represented by the formula (1). In detail, the Tafel gradient is lower than the first reference value in the range of the Fe ratio of 0.2 or less, and changes to a curved shape that is convex downward as the Fe ratio increases. In the test 2, the NiAl-based alloy containing iron in the range of the Fe ratio of 0.2 or less corresponds to the second NiAl-based alloy.
[0101] 2, from the increasing tendency of the Tafel gradient with respect to the increase in the Fe ratio in the range of 0.1 to 0.2, it is considered that the Tafel gradient increases with the increase in the Fe ratio even in the range exceeding 0.2, and reaches the first reference value when the Fe ratio exceeds about 0.35. Therefore, it can be inferred that the Raney nickel obtained from the second NiAl-based alloy containing iron in the range of the Fe ratio of 0.35 or less exhibits higher oxygen generation activity than the Raney nickel obtained from the NiAl-based alloy in which the Co ratio and the Fe ratio are both 0.
[0102] From the above results, it can be seen that the Raney nickel obtained from the second NiAl-based alloy containing cobalt in the Co ratio range of 0.3 to 1.5 and containing iron in the Fe ratio range of 0.35 or less has a higher oxygen generating activity than the Raney nickel obtained from the NiAl-based alloy not containing cobalt or iron. It can also be seen that the Raney nickel obtained from the second NiAl-based alloy containing cobalt in the Co ratio range of 0.3 to 1.5 and containing iron in the Fe ratio range of 0.2 or less has an improved effect of oxygen generating activity due to the inclusion of cobalt. In addition, since the Tafel gradient has a minimum value near the Fe ratio of 0.1, it can be seen that the Raney nickel obtained from the second NiAl-based alloy containing iron in the Fe ratio range of 0.05 to 0.15 among the second NiAl-based alloys exhibits particularly high oxygen generating activity.
[0103] Next, the technical ideas that can be understood from the above embodiment will be described below. [Aspect 1] A method for producing an electrode material for use in an electrode of a water electrolysis device, comprising the steps of: A method for producing an electrode material, comprising an alkali treatment step of obtaining Raney nickel by eluting aluminum from the NiAl-based alloy by treating the NiAl-based alloy with an alkali substance. The NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x (where x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0 ≤ y ≤ 0.35).
[0104] [Aspect 2] The method for producing an electrode material according to Aspect 1, wherein x is a value satisfying 1.0 ≤ x ≤ 1.5. [Aspect 3] The NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x (where x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0 < y ≤ 0.35). The method for producing an electrode material according to Aspect 1 or Aspect 2.
[0105] [Aspect 4] The method for producing an electrode material according to Aspect 1 or Aspect 2, wherein y is a value satisfying 0.05 ≤ y ≤ 0.1.
[0106] [Aspect 5] The NiAl-based alloy has a composition formula Al4Ni (3-x) Co x (where x is a value satisfying 0.3 ≤ x ≤ 1.5). The method for producing an electrode material according to Aspect 1.
[0107] [Aspect 6] The NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe y Co x (where x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0 < y ≤ 0.35). The method for producing an electrode material according to Aspect 1.
[0108] [Aspect 7] The NiAl-based alloy has a composition formula Al4Ni (3-(x+y)) Fe yCo x (x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0.05 < y ≤ 0.15.) The method for producing an electrode material according to aspect 6, which is an alloy represented by
[0109] [Aspect 8] The alkali treatment step includes a treatment of reacting an alkaline aqueous solution, which is an aqueous solution of the alkali substance, with the NiAl-based alloy at a temperature of 100°C or higher. The alkali substance is an alkali metal hydroxide. The method for producing an electrode material according to any one of aspects 1 to 7, wherein the concentration of the alkaline aqueous solution is 3M or higher.
[0110] [Aspect 9] The alkali treatment step includes a treatment of reacting an alkaline aqueous solution, which is an aqueous solution of the alkali substance, with the NiAl-based alloy at a temperature of 140°C or higher. The alkali substance is an alkali metal hydroxide. The method for producing an electrode material according to aspect 8, wherein the concentration of the alkaline aqueous solution is 14M or higher.
[0111] [Aspect 10] The method for producing an electrode material according to any one of aspects 1 to 9, which has an oxidation step of oxidizing the surface of the Raney nickel obtained by the alkali treatment step.
[0112] [Aspect 11] An electrode material used for an electrode of a water electrolysis device, characterized by containing Raney nickel in which the molar ratio of nickel, iron, and cobalt (nickel:iron:cobalt) is (3 - (x + y)):y:x (x and y are values satisfying 0.3 ≤ x ≤ 1.5 and 0 ≤ y ≤ 0.35).
[0113] [Aspect 12] The electrode is an anode, and the electrode material according to aspect 11, wherein the Tafel slope is 70 to 150 mV / dec.
Claims
1. A method for producing an electrode material for use in an electrode of a water electrolysis device, comprising the steps of: an alkali treatment step of treating a NiAl-based alloy with an alkali substance to dissolve aluminum from the NiAl-based alloy to obtain Raney nickel; The NiAl-based alloy has the composition formula Al 4 Ni (3-(x+y)) Fe y Co x (x and y are values satisfying 0.3≦x≦1.5, 0≦y≦0.35).
2. The NiAl-based alloy has the composition formula Al 4 Ni (3-x) Co x 2. The method for producing an electrode material according to claim 1, wherein the alloy is represented by the formula: (x is a value satisfying 0.3≦x≦1.5).
3. The NiAl-based alloy has the composition formula Al 4 Ni (3-(x+y)) Fe y Co x 2. The method for producing an electrode material according to claim 1, wherein the alloy is represented by the formula: (x and y are values that satisfy 0.3≦x≦1.5 and 0<y≦0.35).
4. The NiAl-based alloy has the composition formula Al 4 Ni (3-(x+y)) Fe y Co x 4. The method for producing an electrode material according to claim 3, wherein the alloy is represented by the formula: (x and y are values satisfying 0.5≦x≦1.5 and 0<y≦0.2).
5. The NiAl-based alloy has the composition formula Al 4 Ni (3-(x+y)) Fe y Co x 4. The method for producing an electrode material according to claim 3, wherein the alloy is represented by the formula: (x and y are values that satisfy 0.3≦x≦1.5 and 0.05<y≦0.15).
6. The alkaline treatment step includes a treatment of reacting an alkaline aqueous solution, which is an aqueous solution of the alkaline substance, with the NiAl-based alloy at a temperature of 100° C. or higher, the alkaline substance is an alkali metal hydroxide; The method for producing an electrode material according to any one of claims 1 to 5, wherein the concentration of the alkaline aqueous solution is 3M or more.
7. The alkaline treatment step includes a treatment of reacting an alkaline aqueous solution, which is an aqueous solution of the alkaline substance, with the NiAl-based alloy at a temperature of 140° C. or higher, the alkaline substance is an alkali metal hydroxide; The method for producing an electrode material according to claim 6, wherein the concentration of the alkaline aqueous solution is 14M or more.
8. The method for producing an electrode material according to any one of claims 1 to 5, further comprising an oxidation step of oxidizing a surface of the Raney nickel obtained in the alkali treatment step.
9. An electrode material used in an electrode of a water electrolysis device, An electrode material comprising Raney nickel having a molar ratio of nickel, iron, and cobalt (nickel:iron:cobalt) of (3-(x+y)):y:x (x and y are values that satisfy 0.3≦x≦1.5, 0≦y≦0.35).
Citation Information
Patent Citations
Defect inspection device
JP1989028837A